Design, fabrication and performance evaluation of a sprinkler system (2009)
Keeping lawns and gardens green in the dry season is very difficult. In many establishments, irrigation has been carried out manually. The objective of this project is to design and produce a sprinkler system to irrigate as required. A sprinkler system with an output capacity of 1.42 litres/sec, was designed, fabricated from aluminium and tested. A one horse power pump was selected to accommodate more heads. The sprinkler radius of throw (r) and wetted diameter of coverage(D) were 7m and 14m respectively. The wetted area covered by the sprinkler system was approximately 150m2. The optimum performance of the sprinkler system was at the trajectory angles of 18° to 24°. During testing, an average uniformity coefficient of 85 and percentage distribution uniformity of90% were attained.